Geo-policy and Geo-psychology as Cultural Determinants of Ukrainian Religion, Mentality and National Security - Levyk, Bogdan; Aleksandrova, Olena; Khrypko, Svitlana; Iatsenko, Ganna (Journal of History Culture and Art Research, 2020)
The interconnection between national religious, mental features and geopolitical, geo-psychological factors regarding national security is considered in the paper. The direct and indirect impact of geo-policy and geo-psychology on religious culture, world view, and mentality of the Ukrainian nation is determined. The existence of stable marginal tendencies, that are inherent in Ukrainian culture and mentality, is highlighted. The main concept of the study was formed in the following statement – the geopolitical circumstances (enhanced by the constant presence of internal territorial “borderline”) were not in favor of national unity in the Ukrainian history. The situation caused “instability” and “split” of Ukrainian being as well as national mentality displays. The marginal tendencies of Ukrainian mentality are derived from the geopolitical factor of national being. The dual nature of legal and cultural aspects is presented in the process of the national security establishment. Mental, cultural, and historical memory able to imprint every moment that is beyond legal documents’ capacity, is distinguished within the context. The abovementioned memory becomes a basis for the national security idea’s realization. The initial aim of the paper is to follow geopolitical and geo-psychological features of national, mentality, religious culture and ideas of national security through structural analysis and hermeneutic methodology; to represent the unique “borderline” of Ukrainian geopolitical, cultural, and mental being; to highlight the character and sources of marginal tendencies in Ukrainian spiritual culture. The additional goal is to demonstrate that the legal establishment of national security principles should be based on the cultural and mental factors.